1978
DOI: 10.1111/j.1600-0528.1978.tb01149.x
|View full text |Cite
|
Sign up to set email alerts
|

Age‐standardized incidence rates of ameloblastoma and dentigerous cyst on the Witwatersrand, South Africa

Abstract: Although a great deal is known about the incidence of cancer, including oral cancer, no such study has been done on odontogenic tumors and jaw cysts. There are therefore no standardized data which would allow for comparative incidences in different countries and between different groups. In the present study, cases of ameloblastomas and dentigerous cysts derived from the records of all the hospital pathology departments and private pathology practices on the Witwatersrand, were recorded for the 10-year period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 6 publications
4
50
0
4
Order By: Relevance
“…[8][9][10] Radiographic studies have reported cyst development in impacted third molars to occur at rates between 1% and 1.6% and epidemiological studies have reported the rates as between 0.0002% and 2.31%. [10][11][12][13] However, radiographic and clinical analysis of dental follicles may not always agree with histopathologic findings, [14][15][16][17][18] and the absence of symptoms does not necessarily imply the absence of pathology. [18] Miller and Bean suggested that disease may be present in minute follicular spaces, whereas areas of enlarged radiolucency may be histologically normal, making biopsy imperative.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Radiographic studies have reported cyst development in impacted third molars to occur at rates between 1% and 1.6% and epidemiological studies have reported the rates as between 0.0002% and 2.31%. [10][11][12][13] However, radiographic and clinical analysis of dental follicles may not always agree with histopathologic findings, [14][15][16][17][18] and the absence of symptoms does not necessarily imply the absence of pathology. [18] Miller and Bean suggested that disease may be present in minute follicular spaces, whereas areas of enlarged radiolucency may be histologically normal, making biopsy imperative.…”
Section: Discussionmentioning
confidence: 99%
“…Su incidencia según Larsson y Alteren es de 0,6 casos por millón (3) , aunque otros como Shear y Sign, encontraron cantidades de 0,31 casos por millón (4) .…”
Section: Introductionunclassified
“…According to Regezi et al, [14] Shear and Singh, [15] and Weir et al, [16] the incidence of ameloblastoma associated with impacted third molar was found to be 0.14%, 2% and 0.41% respectively. A study done by Shin et al, [17] who reported that 76.4%, 17.6% and 5.71% showed dentigerous cyst, OKC and ameloblastoma.…”
Section: Section: Dentistrymentioning
confidence: 99%